Feasibility and efficacy of progressive electrostimulation strength training for competitive tennis players - Maffiuletti, N. A.; Bramanti, J.; Jubeau, M.; Bizzini, M.; Deley, G.; Cometti, G. (The Journal of Strength and Conditioning Research, 2009)
The purpose of this preliminary study was to show the feasibility of electrostimulation (ES) strength exercise incorporated into tennis sessions during the preparatory season of competitive players, and its impact on anaerobic performance. Twelve tennis players (5 men, 7 women) completed 9 sessions of quadriceps ES (duration: 16 minutes; frequency: 85 Hz; on-off ratio: 5.25-25 seconds) during 3 weeks. The ES sessions were integrated into tennis training sessions. Subjects were baseline tested and retested 1 (week 4), 2 (week 5), 3 (week 6), and 4 weeks (week 7) after the ES training program for maximal quadriceps strength, vertical jump height, and shuttle sprint time. Participants were able to progressively increase ES current amplitude and evoked force throughout the 9 training sessions, with an optimal treatment compliance of 100%. Maximal quadriceps strength significantly increased during the entire duration of the experiment (p < 0.001). Countermovement jump height at week 5 (+5.3%) and week 6 (+6.4%) was significantly higher than at baseline (p < 0.05). In addition, 2 × 10-m sprint time at week 6 was significantly shorter (-3.3%; p = 0.004) compared with pretraining. The 3-week ES strength training program was successfully incorporated into preseason tennis training with a linear progression in all training parameters. Throughout the study period, a delayed enhancement of anaerobic power and stretch-shortening cycle performance was observed. Progressive ES strength training may be safely included in the early tennis season and can lead to improvements in the anaerobic performance of men and women players.